Using Language Games to Teach Grammar and Engage Fourth-Grade Students in the English Class (2023)
ABSTRACT: This project was an action research developed in Institucion Educativa Dinamarca in Medellín that had the main purpose of exploring how language games can help fourth-grade students to engage with the English class and learn the grammar topics. In order to do this exploration, an action plan was designed and implemented and classes were guided by a methodology organized by stages of exploring language, practicing topics and playing language games. Students had to design and present at the end of the term an album project about themselves putting into practice and in context all the grammar topics and vocabulary learned during the classes. Data was collected through student-teacher journal entries, one students’ diagnostic activity, two students' self- assessments, and the students' written final project. The data analysis showed that the methodology accompanied by language games was useful for promoting students’ engagement in the class, increasing their interest in the English topics, facilitating students’ interactions, and also expanding their lexical repertoire and correct use of adjectives and verbs when building sentences.